Impotência sexual masculina - Henckel, Marciela (2009)
The objective of this thesis is to describe research being done on adult male impotence. Clinical situations with manifestations of erectile dysfunction, which lead one to conceive of a psychopathology of impotence, allow an approach with several different perspectives. This research is being carried out from a psychoanalytic perspective and is being developed within the field of fundamental psychopathology. The text has five chapters. First we present a methodology based on the clinical method, where we describe an investigation which began with masters work and a masters degree, and moved on to the area of doctoral studies. This historical path was possible due to the enigmas that the clinical work produced, permitting articulation between aspects that originally consisted of inhibition in an individual s early childhood and later developed into impotence in adult life. The chapter on psychic and sexual impotence in men is comprised of discussions of clinical cases. The situations related to treatment led to formulations on the nature of inhibition in each case. We thus conceived that there is both a specific and a generalized inhibition, as developed by Freud when dealing with this notion. In terms of specific inhibition, desire is blocked, whereas, in generalized inhibition, the subject's capacity to desire is put into doubt. This distinction would seem to be essential for listening and conducting treatment in cases where the disappearance of sexual desire leads one to recognize the existence of psychic suffering